Genetic landscape of FOXC2 mutations in lymphedema-distichiasis syndrome: Different mechanism of pathogenicity for mutations in different domains. (September 2022) - Jiang, Lingxi; Ren, Weiming; Xie, Chunbao; Duan, Suyang; Dai, Chao; Wei, Yao; Luo, Dongyan; Wang, Tingting; Gong, Bo; Liu, Xiaoqi; Yang, Zhenglin; Ye, Zimeng; et al.
Abstract: Lymphedema-dissociated syndrome (LDS), of which the pathogenesis is not fully understood, afflicts many patients. In this study, we investigated the effect of FOXC2 gene loss-of-function on the development of LDS disease. Two Han Chinese families with LDS were recruited in this study, pathogenic mutations were identified by Sanger sequencing. Reverse-transcription PCR, subcellular localization, dual fluorescein enzymes, and other in vitro experiments were used to study the functional effects of eight FOXC2 mutations. Two pathogenic FOXC2 duplication mutations (c.930_936dup and c.931-937dup) were identified in the two families. Both mutations caused uneven distribution in the nucleus and a chromatin contraction phenotype, weakening the DNA binding activity and transcription activity. We then performed functional analysis on six additional mutations in different domains of FOXC2 that were reported to cause LDS. We found mutations located in the forkhead domain and central region dramatically reduced the transactivation ability, while mutations in activation domain-2 enhanced this ability. All 8 mutations down-regulated the transcription of ANGPT2 and affected the activity of the ERK-RAS pathway, which may cause abnormal formation of lymphatic vessels. Our findings also showed that all 8 mutations decreased the ability of interaction between FOXC2 and the Wnt4 promoter, suggesting mutations in FOXC2 may also affect the Wnt4-Frizzled-RYK signaling pathway, leading the abnormal differentiation of the meibomian glands into hair follicle cells during the embryonic period and causing distichiasis. This study expanded and revealed the potential pathogenesis mechanism. Highlights: We identified two pathogenic variants in LDS and explored the function of multiple mutations in different domains of FOXC2.